PERBAIKAN SIFAT KIMIA RED MUD(RM) DENGAN MENGGUNAKAN BAKTERI PROBIOTIK: PERBAIKAN SIFAT KIMIA RED MUD(RM) DENGAN MENGGUNAKAN BAKTERI PROBIOTIK - marini, lelly; Hariyani, susi; Anggraini, irene (RETENSI, 2021)
ed mud (RM) is waste from a series of bauxite mining processes, with the amount of RM producedaround 1.2 – 1.4 tons for every 1 tonne of alumina produced. RM has chemical properties that are quitedangerous because in addition to containing a lot of non-degradable metals, it also contains a strong base witha pH of around 13-14. If released in its original condition, RM is very dangerous because it could cause waterand soil pollution in the mining environment and could cause disease in humans. All the time, the handling ofRM is by making tailing dam or piling up the subsoil of the highway in the area around the mine which costs alot of money to restore the pH close to neutral before use because the requirement to be released into theenvironment around the allowable pH value is a minimum of 9. Therefore, in this study, the author uses asolution, namely by utilizing the biological activity of probiotic bacteria microorganisms, it could live in analkaline environment and are safe for humans and environmentally friendly. By mixing RM with activatedprobiotic bacteria which will be carried out direct observation of the sample and measuring the pH value. Witha total sample of 27 samples based on variations in the number of active probiotic bacteria mixed and theincubation time of bacteria, the results showed that the more active probiotic bacteria were mixed into the RMand the longer the incubation time of the bacteria, the pH indicator showed close to neutral, namely 8-9. It isalso supported by direct observations based on shape, color, smell and touch, showing that the harmfulchemical properties of RM are decreasing.